2009
DOI: 10.1183/09031936.00091408
|View full text |Cite
|
Sign up to set email alerts
|

Different respiratory phenotypes are associated with isocyanate exposure in spray painters

Abstract: Associations have been observed between exposure to isocyanates, consisting mainly of oligomers, and respiratory symptoms and isocyanate specific sensitisation in spray painters. The aim of the present study was to assess associations between isocyanate exposure and more objective respiratory effect measures such as bronchial hyperresponsiveness (BHR), baseline spirometry and exhaled nitric oxide (eNO) in a subset of spray painters.Methacholine challenge and eNO measurements were performed in 229 workers. Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The use of cleaning products in spray form has increased in past decades [1]. The harmful effect of products in spray form at home [2], or used by spray painters [3], machine workers [4], or in agriculture [5] at work, have been observed in several diseases. Bello et al [6,7], studying detailed tasks among cleaners, classified the use of cleaning sprays as high risk for inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cleaning products in spray form has increased in past decades [1]. The harmful effect of products in spray form at home [2], or used by spray painters [3], machine workers [4], or in agriculture [5] at work, have been observed in several diseases. Bello et al [6,7], studying detailed tasks among cleaners, classified the use of cleaning sprays as high risk for inhalation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, isocyanates, epoxy resins, and methyl methacrylate have been reported to cause or aggravate asthma [NIOSH 2004, Hannu et al 2009, Borak et al 2011. Isocyanates have been studied extensively in the literature, and in addition to asthma, have been associated with hypersensitivity pneumonitis, obstructive lung disease, non-asthmatic neutrophilic bronchitis, and contact dermatitis [NIOSH 2004, Pronk et al 2009, Pala et al 2011. One of the facility's employees was diagnosed with obliterative bronchiolitis, a disease in which the lung's smallest airways are irreversibly scarred, leading to cough and shortness of breath.…”
Section: Discussion Health Effectsmentioning
confidence: 99%
“…This worker had been potentially exposed to isocyanates during a spill response prior to the onset of symptoms. Some isocyanates are associated with asthma, asthma-like symptoms, and other obstructive lung disease [Pala et al 2011;Pronk et al 2009]. Chemical sensitivity has also been described in the literature; it has been associated with several chemicals used at the plant, including di-isocyanates [Mapp et al 1988].…”
Section: Document Reviewmentioning
confidence: 99%
“…Tarlo et al [11] and Pronk [12] reported a negative association between atopy and asthma development, whereas others found no evidence of an association [13] or a positive one [14]. …”
Section: The Atopic Status In Occupational Asthmamentioning
confidence: 99%